Increasing the Germination Power of Chinese Cabbage through Local Ameliorants in Degraded Soil Media Post-Tin Mining - Helda Susianti; Dora Palupi; Sandrina Lestari (SINTA Journal (Science, Technology, and Agricultural), 2025)
The use of local ameliorants has the potential to be an effective solution in improving the quality of post-tin mining soil that is poor in nutrients and has a coarse texture. This study aims to analyze the effect of oil palm bunch ash, coconut shell ash, and chicken manure on the germination of two kale varieties (Nemo and Nita) in degraded media. The study used a two-factor Completely Randomized Design (CRD) at the Precision Agriculture Laboratory of the Bangka Belitung State Manufacturing Polytechnic. The parameters observed included plumule length, radicle, fresh weight of seedlings, fresh weight of roots, and dry weight of roots. The results showed that the percentage and germination capacity did not differ significantly between treatments. However, radicle length, fresh weight, and dry weight of seedlings showed a significant effect, with the best response achieved by the coconut shell ash and oil palm bunch ash treatments. Local ameliorants also caused positive changes in soil physical properties, especially in the color and texture of the media. In conclusion, local ameliorants proved effective in improving the initial conditions of post-mining soil and successfully supported kale germination.